Exploring motivational design and motivation types facilitated by an online support system for learning literature - Adzuhaidah M. Taha,; Thang, Siew Ming (Penerbit UKM, 2014)
This paper is a study designed to explore the influence of an Online Support System for learning Literature (LitOSS) on a group of twenty-five Form 4 Malaysian students who generally perceived English Literature as difficult and uninteresting. This asynchronous mode of learning was introduced with the intention of enhancing the students‟ motivation to learn English literature through a blended learning environment. LitOSS featured seven literature topics encompassing poems, short stories and novel, presented in the forms of online text-based materials, graphics and videos. This study was framed by the Social Cognitive Theory (SCT) of language learning, Keller‟s (1987) Attention, Relevance, Confidence and Satisfaction (ARCS) Model and the Social Cognitive Model of Motivation (SCMM). The motivational design of the system and the prevalent types of motivation facilitated by the system were measured using two sets of questionnaires (i.e. the adapted versions of WebMac Sr. 4.0 and Motivated Strategies for Learning Questionnaire (MSLQ)) and a focus group interview. Findings from the study support the prediction that LitOSS would significantly enhance students‟ motivation to learn literature due to its highly motivating design. It was also discovered that not only did the system promote self-efficacy and a high control of learning, it also motivated the students extrinsically and intrinsically.